A novel trigeneration system using geothermal heat source and liquefied natural gas cold energy recovery: Energy, exergy and exergoeconomic analysis. (April 2018) - Ghaebi, Hadi; Parikhani, Towhid; Rostamzadeh, Hadi
Abstract: This paper deals with the energy, exergy, and exergoeconomic analysis of a novel trigeneration system working with geothermal heat source and liquefied natural gas (LNG) cold energy recovery as thermal sink. The proposed trigeneration system is constructed based on the absorption refrigeration cycle (ARC). Due to the high ammonia concentration at condenser outlet of ARC, a heat pump system is employed for heating production, while LNG cold energy is used for recovering the latent heat of the basic solution from the condenser as heat source as well as for producing power output. A comprehensive thermodynamic modeling of the proposed system is presented and the performance of the system is investigated based on the following performance criteria: net power output, cooling output, heating output, thermal efficiency, exergy efficiency and sum unit cost of the product (SUCP) of the system. In this respect, the simulation revealed that the net power output, cooling output, heating capacity, thermal efficiency, exergy efficiency and total SUCP of the system can be calculated 405.1 kW, 1109 kW, 35.3 kW, 85.92%, 18.52%, and 68.76 $/GJ, respectively, under the proposed constrain variables. In addition, the irreversibility of each component and overall system are presented showing that condenser accounts for the highest exergy destruction among all components which constitutes around 55.51% of the overall exergy destruction rate of the system. Moreover, a comprehensive parametric study is conducted to investigate the effects of some key parameters on the main performance criteria. It is observed that one can obtain a higher thermal efficiency at high evaporator temperature or at low condenser temperature, heating unit temperature and absorber temperature; while a higher exergy efficiency can be obtained at high evaporator temperature or at low absorber and condenser temperatures. In addition, a lower total cost of product of the system can be obtained at high heating unit and evaporator temperatures or low absorber and condenser temperatures. Moreover, it is found that the overall performance of system can be optimized based on the generator hot pinch point temperature difference as well as geothermal inlet temperature. Highlights: To propose a novel trigeneration system using geothermal energy as heat source and LNG cold energy as thermal sink. To present energy, exergy and exergoeconomic evaluations of the proposed system. To present a comprehensive parametric study of some key parameters of the proposed system.